TEACHING ENGLISH PHRASEOLOGICAL UNITS IN IMPROVING SPEAKING SKILLS - Bahriddinova, Yulduzxon (Журнал иностранных языков и лингвистики, 2021)
This article discusses teaching English phraseological units in improving speaking skills and it tells about some methods and teaching technologies of phraseological units to students who learn English as a foreign language